Biological control of strawberry grey mold disease caused by Botrytis cinerea mediated by Colletotrichum acutatum extracts - Tomas-Grau, Rodrigo H.; Hael Conrad, Veronica; Requena-Serra, F.J.; Perato, Silvia Marisa; Caro, María del Pilar; Salazar, Sergio Miguel; Díaz Ricci, Juan Carlos (Springer, 2020)
Despite the negative impact on human, animal and environmental health, synthetic fungicides are the most common agrochemicals used to control Botrytis cinerea, the causal agent of grey mold disease. Strawberry plants are very susceptible to many pathogens, especially the necrotrophic fungus B. cinerea. In this work, we show that two fungal extracts obtained from a local isolate of Colletotrichum acutatum (M11) can protect strawberry plants against grey mold. Fungal culture filtrate (CF), and the axenic semi-purified culture filtrate (ACF) induce local and systemic acquired resistance against B. cinerea, and reduce fungal virulence. These results suggest that CF and ACF can be used as effective ingredients of bioproducts to control grey mold in strawberry crop. We also show that the elicitor peptide flg22 is effective to confer strawberry plants local and systemic protection against B. cinerea but only when applied 24 h prior to the infection.